TOTAL HYDROGENATION OF BIOMASS-DERIVED FURFURAL OVER RANEY NICKEL-CLAY NANOCOMPOSITE CATALYSTS - Rodiansono Rodiansono; Takayoshi Hara; Shogo Shimazu (Indonesian Journal of Chemistry, 2013)
Inexpensive Raney Ni-clay composite (R-Ni/clay) catalysts exhibited excellent activity and reusability in the total hydrogenation of biomass-derived furfural into tetrahydrofurfuryl alcohol under mild conditions. For the Raney Ni-bentonite (R-Ni/BNT) catalysts, the complete reaction was achieved at 393 K, 180 min giving almost 99% yield of tetrahydrofurfuryl alcohol. The R-Ni/BNT catalyst was found to be reusable without any significant loss of activity and selectivity for at least six consecutive runs.